Sunni and Shiite Political Thought of Islam State Relationship: A Comparison between Abdurrahman Wahid of Indonesia and Ayatollah Khomeini of Iran - Ahmad Ali Nurdin; Ahmad Tholabi Kharlie (Journal of Asian Social Science Research, 2019)
This paper discusses how the Indonesian Sunni Muslim leader Abdurrahman Wahid and the Iranian Shiite Muslim leader Ayatollah Khomeini responded to the debate about the relationship between Islam and the state. Their responses impacted on the struggle of Indonesian and Iranian Muslims in considering the ideological basis of Indonesian and Iranian states. On the one hand, Wahid with his educational and social background and Indonesian political context rejected the concept of an Islamic state. He did not agree with the formalization of Islamic sharia. To implement his idea, he promoted the idea of Pribumisasi Islam. For Wahid, islamization was not arabization. Khomeini, on the other hand, believed that Islam is a religion that has complete laws and way of life including social rules. According to Khomeini, to effectively implement these rules, Muslims need to have executive power. In Khomeini’s view, when the Quran calls for Muslims to obey Allah, the messenger, and ulil amri, this means that Allah instructs Muslims to create an Islamic state. To realise his views, Khomeini proposed the doctrine of Velayat-e al Faqeeh. Thus, different religious-political contexts of these two leaders contributed to their different responses to the relationship between Islam and the state.